2008
DOI: 10.1103/physrevc.78.044905
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle degrees of freedom versus the perfect fluid as descriptors of the quark-gluon plasma

Abstract: The hot nuclear matter created at the Relativistic Heavy Ion Collider (RHIC) has been characterized by near-perfect fluid behavior. We demonstrate that this stands in contradiction to the identification of QCD quasi-particles with the thermodynamic degrees of freedom in the early (fluid) stage of heavy ion collisions. The empirical observation of constituent quark "nq" scaling of elliptic flow [1] is juxtaposed with the lack of such scaling behavior in hydrodynamic fluid calculations followed by Cooper-Frye fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…It is interesting to note that the ideal hydrodynamic results scale at neither low nor intermediate p T . Therefore the observed scaling cannot be a general characteristic of hydrodynamic model calculations [17], although such calculations do show the observed mass ordering in the low p T region. Figures 10 and 11 show the centrality dependence of the scaling properties and the ratios, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is interesting to note that the ideal hydrodynamic results scale at neither low nor intermediate p T . Therefore the observed scaling cannot be a general characteristic of hydrodynamic model calculations [17], although such calculations do show the observed mass ordering in the low p T region. Figures 10 and 11 show the centrality dependence of the scaling properties and the ratios, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Further detailed analyses of the hadron mass dependence of v 2 suggest that the system has been in the deconfined state with constituent quark degrees of freedom prior to hadronization [11][12][13]. Furthermore, results of multistrange hadron transverse momentum distributions and v 2 indicate that the system reached thermalization at the partonic stage [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of resonance decays on pion elliptic flow was also studied in Ref. [14], where the authors assumed that direct pions follow the KE T -scaling and then found the scaling still holds at the 10% level when resonances are included.…”
Section: Discussionmentioning
confidence: 99%
“…This hampers attempts to extend the description into the low-p T regime where thermalization is believed to prevail. This has become a more pressing issue once it was realized that CQNS can be generalized to encompass both low and intermediate p T if v 2 is plotted versus transverse kinetic energy, KE T ≡ m T − m, where m T = (p 2 T + m 2 ) 1/2 is the hadron's transverse mass [12][13][14][15][16][17]. In this representation, elliptic-flow data for all ob-served hadrons fall onto one universal curve for v 2 /n q versus KE T /n q [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been emphasized in [27] that a quasi-particle description of the QGP may not be valid. A quasi-particle picture is even less likely to capture the physics of strongly coupled N = 4 super-Yang-Mills, where the weakly coupled degrees of freedom are manifest only in the dual gravitational description.…”
Section: Estimating the Energy Of A Doubled Stringmentioning
confidence: 99%